Acute kidney injury in critical care: complications of hemophagocytic lymphohistiocytosis - Zhao, Mengya; Guan, Yiming; Lin, Jin; Qiu, Yu; Zhao, Shen; Duan, Meili (Frontiers in Immunology, 2024)
Hemophagocytic lymphohistiocytosis (HLH) is an immune dysfunction characterized by an exaggerated and pathological inflammatory response, potentially leading to systemic inflammatory reactions and multiple-organ failure, including renal involvement. HLH can be classified as primary or secondary, with primary HLH associated with genetic mutations affecting cell degranulation capacity, and secondary HLH often linked to infections, tumors, and autoimmune diseases. The pathogenesis of HLH is not fully understood, but primary HLH is typically driven by genetic defects, whereas secondary HLH involves the activation of CD8+ T cells and macrophages, leading to the release of inflammatory cytokines and systemic inflammatory response syndrome (SIRS). The clinical presentation of HLH includes non-specific manifestations, making it challenging to differentiate from severe sepsis, particularly secondary HLH due to infections. Shared features include prolonged fever, hepatosplenomegaly, hematopenia, hepatic dysfunction, hypertriglyceridemia, and hypofibrinogenemia, along with histiocytosis and hemophagocytosis. However, distinctive markers like dual hemocytopenia, hypertriglyceridemia, hypofibrinogenemia, and elevated sCD25 levels may aid in differentiating HLH from sepsis. Indeed, no singular biomarker effectively distinguishes between hemophagocytic lymphohistiocytosis and infection. However, research on combined biomarkers provides insights into the differential diagnosis. Renal impairment is frequently encountered in both HLH and sepsis. It can result from a systemic inflammatory response triggered by an influx of inflammatory mediators, from direct damage caused by these factors, or as a consequence of the primary disease process. For instance, macrophage infiltration of the kidney can lead to structural damage affecting various renal components, precipitating disease. Presently, tubular necrosis remains the predominant form of renal involvement in HLH-associated acute kidney injury (HLH-AKI). However, histopathological changes may also encompass interstitial inflammation, glomerular abnormalities, microscopic lesions, and thrombotic microangiopathy. Treatment approaches for HLH and sepsis diverge significantly. HLH is primarily managed with repeated chemotherapy to eliminate immune-activating stimuli and suppress hypercellularity. The treatment approach for sepsis primarily focuses on anti-infective therapy and intensive symptomatic supportive care. Renal function significantly influences clinical decision-making, particularly regarding the selection of chemotherapy and antibiotic dosages, which can profoundly impact patient prognosis. Conversely, renal function recovery is a complex process influenced by factors such as disease severity, timely diagnosis, and the intensity of treatment. A crucial aspect in managing HLH-AKI is the timely diagnosis, which plays a pivotal role in reversing renal impairment and creating a therapeutic window for intervention, may have opportunity to improve patient prognosis. Understanding the clinical characteristics, underlying causes, biomarkers, immunopathogenesis, and treatment options for hemophagocytic lymphohistiocytosis associated with acute kidney injury (HLH-AKI) is crucial for improving patient prognosis.